H-rosette formation in T-cell-proliferative diseases. Issue 5993 (15th November 1975) - Sheldon, P J; Holborow, E J
Abstract : In health up to 6% of human lymphocytes will form rosettes with homologous group O rhesus-negative erythrocytes (H rosettes). Increased numbers of H rosettes were found in T-cell-proliferative diseases-- namely, infectious mononucleosis, Sézary's syndrome, and T-cell leukaemia. H-rosette formation is thus a marker for a subpopulation of T lymphocytes, and this easily performed test of T-cell activation may have clinical value in characterising changes in blood lymphocyte populations in disease.